IDENTIFIKASI BEBAN KERJA UNTUK MENENTUKAN JUMLAH TENAGA KERJA PROJECT MANAGEMENT OFFICE WILAYAH DISTRIBUSI 2 DI PT XYZ DENGAN MENGGUNAKAN METODE FTE (FULL TIME EQUIVALENT) - Nadira Chandra Reyhani (Program Studi Teknik Industri S-1, Fakultas Teknik UPN Veteran Jakarta, 2024)
PT XYZ is a corporation that deals with natural gas transportation and distribution. PT XYZ, particularly the Project Management Office division in distribution region 2, occasionally encounters challenges during the process, like project delays. The project was delayed because of a lack of people and an unequal workload in carrying out job operations at PT XYZ. As a result, measuring workload as a foundation for determining manpower requirements is essential. The Full Time Equivalent (FTE) approach was employed by the researchers in this investigation. After using this approach, it is determined that the workload in distribution area 2 is imbalanced among the 16 operators operating, with 13 having high workload or overload and 3 having moderate workload (fit). The proposed enhancements include adding 8 operators and performing horizontal mutations; the ideal workforce consists of 24 individuals with workloads in the normal (fit) and low (underload) categories. Based on the cost analysis, the option with the lowest cost was picked, namely expanding a workforce of 8 operators, with additional specifics of the monthly expenditures equal to IDR 117,050,000.-.